GE_GERICHTE P/1036/2015 vom 24. Januar 2018 - GE Cour de justice (2018)
ACTE D'ORDRE SEXUEL AVEC UN ENFANT ; CONTRAINTE SEXUELLE ; VIOLATION DU DEVOIR D'ASSISTANCE OU D'ÉDUCATION ; TORT MORAL | CP.123.ch1; CP.123.ch2; CP.187.ch1; CP.189.ch1; CP.219.al1; CP.97; CP.47; CP.49; CP.48.lete; CO.49